Electrochemical Reduction of Uniformly Dispersed Pt and Ag Nanodots on Carbon Fiber Electrodes. (19th October 2009) - Pai, Yi-Hao; Lin, Gong-Ru
Abstract : Electrochemical characterization of the uniformly dispersed Pt and Ag nanodots synthesized after in situ scalable electron-beam reduction on copper grid and carbon-fiber electrode is demonstrated. By employing plasma pretreatment to produce functional organosilicon micronetworks-based reaction sites on copper grid, the size and standard deviation of the electrochemically reduced metallic nanodots can be strictly confined. When detuning the accelerating voltage of electron-beam from 3 to 120 kV, the reshaped nanodot diameter enlarges from12.7 ± 0.8 to18.3 ± 3.6  nm due to the gradual self-aggregation. In comparison with sputtering method, the electroactivity of Pt nanodot covered carbon fiber electrode obtained after electron-beam reduction exhibits a larger electroactive surface (S pt ) of 16.56 cm 2 /mg. The electron-beam reduction provides a better dispersion of the reduced Pt nanodots based catalysts on carbon-fiber electrode, promoting the utilization efficiency of these nanoscale catalyst (defined as the ratio of electroactive to geometric area) from 2.5% to 7%.